2018
DOI: 10.1038/s41467-018-05767-4
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbiota promotes hepatic fatty acid desaturation and elongation in mice

Abstract: Interactions between the gut microbial ecosystem and host lipid homeostasis are highly relevant to host physiology and metabolic diseases. We present a comprehensive multi-omics view of the effect of intestinal microbial colonization on hepatic lipid metabolism, integrating transcriptomic, proteomic, phosphoproteomic, and lipidomic analyses of liver and plasma samples from germfree and specific pathogen-free mice. Microbes induce monounsaturated fatty acid generation by stearoyl-CoA desaturase 1 and polyunsatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
167
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(188 citation statements)
references
References 77 publications
14
167
0
Order By: Relevance
“…We additionally observed augmented adiponectin secretion (Figure 4I), pointing towards improved insulin sensitivity in the WD McB group, further supported by the assessment of insulin tolerance and hepatic gene transcription activity of key metabolic enzymes (Figure 4J-K). Of interest, we observed a >10-fold downregulation of Scd1 in the liver of WD McB -fed mice, the hepatic expression of which is a) regulated by the microbiota 40 and b) instrumental in de novo lipogenesis at the onset of metabolic syndrome 41 .…”
Section: Resultsmentioning
confidence: 85%
“…We additionally observed augmented adiponectin secretion (Figure 4I), pointing towards improved insulin sensitivity in the WD McB group, further supported by the assessment of insulin tolerance and hepatic gene transcription activity of key metabolic enzymes (Figure 4J-K). Of interest, we observed a >10-fold downregulation of Scd1 in the liver of WD McB -fed mice, the hepatic expression of which is a) regulated by the microbiota 40 and b) instrumental in de novo lipogenesis at the onset of metabolic syndrome 41 .…”
Section: Resultsmentioning
confidence: 85%
“…Several studies support the role of gut microbes as potent regulators of hepatic lipid metabolism. Indeed, comparison of hepatic fatty acid metabolism between germ-free and conventionally raised specific-pathogen-free mice has shown that gut microbes impact the MUFA content and PUFA elongation by modifying Scd1 and Elovl5 expression, respectively (Kindt et al, 2018). In addition, alteration of the expression level of genes involved in hepatic lipid metabolism (Srebp1c, Acc, Fas, Scd1, Acat2, Dgat1, Dgat2, Hmgcs, and Hmgcr) has been reported in TLR5-deficient mice (Singh et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The microbiota regulates lipid metabolization and absorption at the level of the intestinal mucosa (Martinez-Guryn et al, 2018). In addition to that, gut microbes can modify hepatic de novo lipogenesis by modulating expression of genes involved in lipid metabolism and by generating short chain fatty acids (SCFA) that are substrates for hepatic lipogenesis (Singh et al, 2015;Kindt et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the correlations between the milk microbiota and its content in FA and Ig were analyzed. Dietary FA can impact the intestinal microbiota composition [63], and vice versa, the metabolites produced by the microbiota can have an impact on lipid metabolism [64]. Recent studies found associations between the FA profile and the microbiota composition in human milk [33,52].…”
Section: Discussionmentioning
confidence: 99%